IMPLEMENTASI PASAL 33 AYAT 3 UUD 1945 DALAM BERBAGAI PERUNDANG-UNDANGAN TENTANG SUMBERDAYA ALAM - Tjok Istri Putra Astiti; Gusti Ayu Putri Kartika; Anak Agung Istri Ari Atu Dewi (University of Udayana, 2015)
This study aims to : 1) determine the translation of Article 33, paragraph 3 of the 1945 Constitution in a variety of legislation on natural resources, 2 ) analyze the synchronization of several provisions in the legislation on the natural resources, espicially related to legal community participation and sanctions, and 3) analyze the implications of insynchroni- zation between the regulations of natural resource. This research is a normative legal research is implemented using the statute approach. The main object of study is the primary legal materials in the form of legislation on natural resources. The results showed that, in principle, the essence of Article 33 paragraph 3 of the 1945 Constitution, about the